Investigating the use of dietary supplements among undergraduate pharmacy students - Yazid, Farah Nabillah; Engku Zam, Engku Nursyamimi; Bedu Hasan, Evana Tashah; Musa, Fatin Aqilah; Hurdy, Nurfadhilah; Atta Abbas, Naqvi; Mohd Taufek, Nor Hidayah (2019)
Introduction: Dietary supplements are commonly used among adult’s population for various indications. Little is known about the common types of dietary supplement used and the monthly expenditure for supplements among pharmacy students. Objectives: The study aimed to investigate the use of dietary supplements among undergraduate pharmacy students in Kuantan, Pahang. Methods: A cross-sectional survey was conducted using a validated Dietary Supplement Questionnaire among undergraduate pharmacy students at International Islamic University Malaysia. Data were analysed using SPSS for descriptive statistics. Results: A total of 372 students participated in the study (age range: 18-25 years), with 45.7% of them took supplements where brands were preferred over generic types. A majority (92.2%) of them did not have any illnesses. The reasons for taking supplements were for general health (38.2%), boosting immunity (18.6%), energy source (9.5%) and enhancing memory (8.8%). The average monthly expenditure for supplement was RM58.73 (USD 14.01). The types of supplements used were multivitamin, evening primrose oil and ginkgo biloba. A majority (68.0%, n=253) of them would recommend supplements with doctors’ advice. They agreed that supplements could prevent chronic diseases (38.8%), were harmless (34.9%), are necessary for all ages (21.3%), and could prevent cancer (5.0%). The sources of information were doctors/pharmacists (33.5%), internet (33.1%) and friends/family/relatives (25.0%). They also reported positive (42.5%), neutral (52.4%) and negative (5.0%) experiences from taking supplements. Conclusion: Dietary supplements were taken by two-fifths of pharmacy students. Further research is needed to evaluate the rational use of supplements among pharmacy students.